Abundance of antibiotic resistance genes and bacterial community composition in wild freshwater fish species - Marti, Elisabet; Huerta, Belinda; Rodríguez-Mozaz, Sara; Barceló, Damià; Marcé, Rafael; Balcázar, Jose Luis (Chemosphere, 2018)
This study was aimed to determine the abundance of four antibiotic resistance genes (blaTEM, ermB, qnrS and sulI), as well as bacterial community composition associated with the intestinal mucus of wild freshwater fish species collected from the Foix and La Llosa del Cavall reservoirs, which represent ecosystems with high and low anthropogenic disturbance, respectively. Water and sediments from these reservoirs were also collected and analyzed to determine the pollution level by antibiotics. The blaTEM gene was only detected in brown trout and Ebro barbel, which were collected from La Llosa del Cavall reservoir. In contrast, the sulI and qnrS genes were only detected in common carp, which were collected from the Foix reservoir. Although the ermB gene was also detected in common carp, the values were below the limit of quantification. Likewise, water and sediment samples from the Foix reservoir had higher concentrations and more classes of antibiotics than those from La Llosa del Cavall. Pyrosequencing analysis of 16S rRNA genes revealed significant differences in bacterial communities associated with the intestinal mucus of fish species. Therefore, these findings suggest that anthropogenic activities are not only increasing the pollution of aquatic environments, but also contributing to the emergence and spread of antibiotic resistance in organisms that inhabit such environments.
Keywords: Antibiotic resistance genes; Aquatic environments; Bacterial community composition; Wild fishes; dept.che

Effects of subinhibitory ciprofloxacin concentrations on the abundance of qnrS and composition of bacterial communities from water supply reservoirs - Marti, Elisabet; Huerta, Belinda; Rodríguez-Mozaz, Sara; Barceló, Damià; Balcázar, Jose Luis; Marcé, Rafael (Chemosphere, 2016)
We used a short-term microcosm approach to investigate the influence of two different subinhibitory concentrations of ciprofloxacin (0.01 and 0.1 μg/ml) on both the abundance of a plasmid-mediated quinolone resistance determinant (qnrS) and the structure and composition of bacterial communities from impaired and pristine water supply reservoirs. The results showed that the abundance of the qnrS gene increases in water samples exposed to both subinhibitory concentrations of ciprofloxacin, especially in water samples from La Llosa del Cavall, which represents the pristine system. Subinhibitory ciprofloxacin concentrations also induced changes in bacterial community composition as indicated by the relative abundances of each operational taxonomic unit (OTU) across treatments. Therefore, our findings may be of significant importance because subinhibitory ciprofloxacin concentrations may promote antibiotic resistance and affect bacterial community composition in environmental settings.
Keywords: Antibiotic resistance genes; Aquatic systems; Bacterial community; Quinolones; Water supply reservoirs; dept.che

Presence of pharmaceuticals in fish collected from urban rivers in the U.S. EPA 2008–2009 National Rivers and Streams Assessment - Huerta, Belinda; Rodriguez-Mozaz, Sara; Lazorchak, Jim; Barcelo, Damia; Batt, Angela; Wathen, John; Stahl, Leanne (Science of The Total Environment, 2018)
Fish are good indicators of aquatic environment pollution because of their capability to uptake pollutants contained in water. Therefore, accumulation of pharmaceutical compounds in freshwater and marine fish and other aquatic organisms has been studied extensively in the last decade. In this context, the present study investigates the occurrence of pharmaceutical compounds in wild fish from 25 polluted river sites in the USA, downstream from wastewater treatment plants (WWTPs). Sample sites constitute a subset of urban rivers investigated in the U.S. EPA's 2008–2009 National Rivers and Streams Assessment. Thirteen pharmaceuticals (out of the twenty compounds analyzed) were quantified in fish fillets at concentrations commonly below 10ngg−1, in accordance with the findings from previous studies in the USA and Europe. The psychoactive drugs venlafaxine, carbamazepine and its metabolite 2-hydroxy carbamazepine were the most prevalent compounds (58%, 27% and 42%, respectively). This group of drugs is highly prescribed and rather resistant to degradation during conventional treatment in WWTPs as well as in natural aquatic environments. Salbutamol, a drug used to treat asthma, and the diuretic hydrochlorothiazide were also frequently detected (in >20% of the samples). Occurrence of six pharmaceutical families due to chronic exposure at environmental concentrations in water was detected in eight fish species.
Keywords: Accumulation; Fish; Pharmaceuticals; Trophic level; dept.che

Bioaccumulation and trophic magnification of pharmaceuticals and endocrine disruptors in a Mediterranean river food web - Ruhí, Albert; Acuña, Vicenç; Barceló, Damià; Huerta, Belinda; Mor, Jordi-Rene; Rodríguez-Mozaz, Sara; Sabater, Sergi (Science of The Total Environment, 2016)
Increasing evidence exists that emerging pollutants such as pharmaceuticals (PhACs) and endocrine-disrupting compounds (EDCs) can be bioaccumulated by aquatic organisms. However, the relative role of trophic transfers in the acquisition of emerging pollutants by aquatic organisms remains largely unexplored. In freshwater ecosystems, wastewater treatment plants are a major source of PhACs and EDCs. Here we studied the entrance of emerging pollutants and their flow through riverine food webs in an effluent-influenced river. To this end we assembled a data set on the composition and concentrations of a broad spectrum of PhACs (25 compounds) and EDCs (12 compounds) in water, biofilm, and three aquatic macroinvertebrate taxa with different trophic positions and feeding strategies (Ancylus fluviatilis, Hydropsyche sp., Phagocata vitta). We tested for similarities in pollutant levels among these compartments, and we compared observed bioaccumulation factors (BAFs) to those predicted by a previously-developed empirical model based on octanol–water distribution coefficients (Dow). Despite a high variation in composition and levels of emerging pollutants across food web compartments, observed BAFs in Hydropsyche and Phagocata matched, on average, those already predicted. Three compounds (the anti-inflammatory drug diclofenac, the lipid regulator gemfibrozil, and the flame retardant TBEP) were detected in water, biofilm and (at least) one macroinvertebrate taxa. TBEP was the only compound present in all taxa and showed magnification across trophic levels. This suggests that prey consumption may be, in some cases, a significant exposure route. This study advances the notion that both waterborne exposure and trophic interactions need to be taken into account when assessing the potential ecological risks of emerging pollutants in aquatic ecosystems.
Keywords: Bioaccumulation factors (BAFs); Biomagnification; Contaminants; Macroinvertebrates; Pharmaceutical drugs; dept.che

Fluvial biofilms exposed to desiccation and pharmaceutical pollution: New insights using metabolomics - Serra-Compte, Albert; Corcoll, Natàlia; Huerta, Belinda; Rodríguez-Mozaz, Sara; Sabater, Sergi; Barceló, Damià; Álvarez-Muñoz, Diana (Science of The Total Environment, 2018)
In many arid and semi-arid systems, biological communities in river ecosystems are submitted to flow interruption and desiccation, as well as to the impact of urban wastewaters. In this work, we studied (using a LC-LTQ-Orbitrap) the metabolomic response of biofilm communities exposed to both hydrological and chemical stressors. Fluvial biofilms were exposed to a mixture of 9 pharmaceuticals at a total concentration of 5000ng/L (mimicking concentrations and compounds found in polluted aquatic environments) and/or to seven days of desiccation, under laboratory conditions. The biosynthesis of fatty acids was the main metabolic pathway disrupted in biofilms. Endogenous biofilm's metabolites (metabolome) altered due to these stressors were identified. The metabolites that significantly changed only due to one of the stressors could be proposed as potential specific biomarkers. A biomarker of pharmaceutical exposure was the lysophosphatidic acid, which decreased a 160%, while for desiccation stearidonic acid (increased 160%), 16-Oxohexadecanoic acid (increased 340%) and palmitoleic acid (decreased 290%) were the biomarkers proposed. Besides, other metabolites showed different responses depending on the treatment, such as palmitic acid, linolenic acid, behenic acid, lignoceric acid and azelaic acid. The Carbon:Phosphorus (C:P) molar ratio increased due to all stress factors, whereas the algal community composition changed mainly due to desiccation. A possible relationship between those changes observed in structural parameters and the metabolome of biofilms was explored. Overall, our findings support the use of metabolomics to unravel at molecular level the effects from chemical and physical stressors on complex microbial communities, such as biofilms, and pinpoint biomarkers of exposure.
Keywords: Biofilms; Biomarkers; Environmental stressors; Metabolomic profiling; dept.che

Anti‐anxiety drugs and fish behavior: Establishing the link between internal concentrations of oxazepam and behavioral effects - Huerta, Belinda; Margiotta‐Casaluci, Luigi; Rodríguez‐Mozaz, Sara; Scholze, Martin; Winter, Matthew J.; Barceló, Damià; Sumpter, John P. (Environmental Toxicology and Chemistry, 2016)
Psychoactive drugs are frequently detected in the aquatic environment. The evolutionary conservation of the molecular targets of these drugs in fish suggests that they may elicit mode of action–mediated effects in fish as they do in humans, and the key open question is at what exposure concentrations these effects might occur. In the present study, the authors investigated the uptake and tissue distribution of the benzodiazepine oxazepam in the fathead minnow (Pimephales promelas) after 28 d of waterborne exposure to 0.8 μg L−1, 4.7 μg L−1, and 30.6 μg L−1. Successively, they explored the relationship between the internal concentrations of oxazepam and the effects on fish exploratory behavior quantified by performing 2 types of behavioral tests, the novel tank diving test and the shelter‐seeking test. The highest internal concentrations of oxazepam were found in brain, followed by plasma and liver, whereas muscle presented the lowest values. Average concentrations measured in the plasma of fish from the 3 exposure groups were, respectively, 8.7 ± 5.7 μg L−1, 30.3 ± 16.1 μg L−1, and 98.8 ± 72.9 μg L−1. Significant correlations between plasma and tissue concentrations of oxazepam were found in all 3 groups. Exposure of fish to 30.6 µg L−1 in water produced plasma concentrations within or just below the human therapeutic plasma concentration (HTPC) range in many individuals. Statistically significant behavioral effects in the novel tank diving test were observed in fish exposed to 4.7 μg L−1. In this group, plasma concentrations of oxazepam were approximately one‐third of the lowest HTPC value. No significant effects were observed in fish exposed to the lowest and highest concentrations. The significance of these results is discussed in the context of the species‐specific behavior of fathead minnow and existing knowledge of oxazepam pharmacology. Environ Toxicol Chem 2016;35:2782–2790. © 2016 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.
Keywords: dept.che

Internal exposure dynamics drive the Adverse Outcome Pathways of synthetic glucocorticoids in fish - Margiotta-Casaluci, Luigi; Owen, Stewart F.; Huerta, Belinda; Rodríguez-Mozaz, Sara; Kugathas, Subramanian; Barceló, Damià; Rand-Weaver, Mariann; Sumpter, John P. (Scientific Reports, 2016)
The Adverse Outcome Pathway (AOP) framework represents a valuable conceptual tool to systematically integrate existing toxicological knowledge from a mechanistic perspective to facilitate predictions of chemical-induced effects across species. However, its application for decision-making requires the transition from qualitative to quantitative AOP (qAOP). Here we used a fish model and the synthetic glucocorticoid beclomethasone dipropionate (BDP) to investigate the role of chemical-specific properties, pharmacokinetics, and internal exposure dynamics in the development of qAOPs. We generated a qAOP network based on drug plasma concentrations and focused on immunodepression, skin androgenisation, disruption of gluconeogenesis and reproductive performance. We showed that internal exposure dynamics and chemical-specific properties influence the development of qAOPs and their predictive power. Comparing the effects of two different glucocorticoids, we highlight how relatively similar in vitro hazard-based indicators can lead to different in vivo risk. This discrepancy can be predicted by their different uptake potential, pharmacokinetic (PK) and pharmacodynamic (PD) profiles. We recommend that the development phase of qAOPs should include the application of species-specific uptake and physiologically-based PK/PD models. This integration will significantly enhance the predictive power, enabling a more accurate assessment of the risk and the reliable transferability of qAOPs across chemicals.
Keywords: Ecophysiology; Environmental sciences; Physiology; dept.che

Effects of flow intermittency and pharmaceutical exposure on the structure and metabolism of stream biofilms - Corcoll, Natàlia; Casellas, Maria; Huerta, Belinda; Guasch, Helena; Acuña, Vicenç; Rodríguez-Mozaz, Sara; Serra-Compte, Albert; Barceló, Damià; Sabater, Sergi (Science of The Total Environment, 2015)
Increasing concentrations of pharmaceutical compounds occur in many rivers, but their environmental risk remains poorly studied in stream biofilms. Flow intermittency shapes the structure and functions of ecosystems, and may enhance their sensitivity to toxicants. This study evaluates the effects of a long-term exposure of biofilm communities to a mixture of pharmaceutical compounds at environmental concentrations on biofilm bioaccumulation capacity, the structure and metabolic processes of algae and bacteria communities, and how their potential effects were enhanced or not by the occurrence of flow intermittency. To assess the interaction between those two stressors, an experiment with artificial streams was performed. Stream biofilms were exposed to a mixture of pharmaceuticals, as well as to a short period of flow intermittency. Results indicate that biofilms were negatively affected by pharmaceuticals. The algal biomass and taxa richness decreased and unicellular green algae relatively increased. The structure of the bacterial (based on denaturing gradient gel electrophoresis of amplified 16S rRNA genes) changed and showed a reduction of the operational taxonomic units (OTUs) richness. Exposed biofilms showed higher rates of metabolic processes, such as primary production and community respiration, attributed to pharmaceuticals stimulated an increase of green algae and heterotrophs, respectively. Flow intermittency modulated the effects of chemicals on natural communities. The algal community became more sensitive to short-term exposure of pharmaceuticals (lower EC50 value) when exposed to water intermittency, indicating cumulative effects between the two assessed stressors. In contrast to algae, the bacterial community became less sensitive to short-term exposure of pharmaceuticals (higher EC50) when exposed to water intermittency, indicating co-tolerance phenomena. According to the observed effects, the environmental risk of pharmaceuticals in nature is high, but different depending on the flow regime, as well as the target organisms (autotrophs vs heterotrophs).
Keywords: Algae; Bacteria; Ecotoxicology; Intermittent rivers; Multiple stressors; Pollution; dept.che